2016
DOI: 10.1007/s11099-016-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic activity of variegated leaves of Coleus × hybridus hort. cultivars characterised by chlorophyll fluorescence techniques

Abstract: Different pigments often occur together and affect photosynthetic characteristics of the respective leaf portions. In this study, photosynthetic activity in variegated leaves of five cultivars of the ornamental and medicinal plant, Coleus × hybridus hort., was estimated by image analysis and point data measurements of major chlorophyll (Chl) fluorescence parameters and related to the amount of photosynthetic pigments measured with a Chl meter or spectrophotometrically in leaf extracts. Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 67 publications
5
27
0
1
Order By: Relevance
“…The variations in chlorophyll a/b ratio rise due to the differences between photosystems I and II (PSI / PSII), as well as to size and composition of the antenna complex of each photosystem that is responsible for light collection. These differences also can be attributed to growing and environmental conditions, as well as to the phenological stage (Cancellier et al, 2011;Borek et al, 2016). For Troyano, there was a reduction of the ratio of chlorophyll a/b, but that was not statistically different from 'Roxo de Valinhos' and PI-189.…”
Section: Resultsmentioning
confidence: 98%
“…The variations in chlorophyll a/b ratio rise due to the differences between photosystems I and II (PSI / PSII), as well as to size and composition of the antenna complex of each photosystem that is responsible for light collection. These differences also can be attributed to growing and environmental conditions, as well as to the phenological stage (Cancellier et al, 2011;Borek et al, 2016). For Troyano, there was a reduction of the ratio of chlorophyll a/b, but that was not statistically different from 'Roxo de Valinhos' and PI-189.…”
Section: Resultsmentioning
confidence: 98%
“…Iron substitutes magnesium and heme is produced instead of Chl (Zhou and Qiu 2005). Greenness index often inversely corresponds with F0, namely, higher greenness index and chemically assayed Chl content correlate with lower F0 values (Baker 2008, Borek et al 2016. The downward trend in SPAD readings for the late cultivar ceased over time, and the time course of changes in F0 was opposite to that of SPAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, even distinct changes in Fv/Fm may be insufficient to accurately assess functioning of the photosynthetic apparatus. Therefore, it is necessary to take other values into account (Bączek-Kwinta et al 2011b, Borek et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Chl fluorescence data, YS retained high Fv/Fm values, suggesting that high Car in YS might be responsible for harvesting light energy. Meanwhile, Borek et al (2016) showed that higher Car in purple parts of Coleus × hybridus hort. cultivars could provide photoprotective effects.…”
Section: Leaf Typementioning
confidence: 99%
“…Similar results have been also observed in some other variegated leaves of Coleus × hybridus hort. cultivars, Hedera helix, Ardisia pusilla, and Scindapsus aureus (Khalekuzzaman et al 2015, Borek et al 2016. According to the Chl fluorescence data, YS retained high Fv/Fm values, suggesting that high Car in YS might be responsible for harvesting light energy.…”
Section: Leaf Typementioning
confidence: 99%